2009
DOI: 10.1002/mrd.21043
|View full text |Cite
|
Sign up to set email alerts
|

Teachings from the egg: New and unexpected functions of RNAs

Abstract: SUMMARYLocalized mRNAs found in specific regions of somatic cells, germ cells, and embryos function through their protein translation products in cell polarization and development. Recent studies on Xenopus and Drosophila eggs and various somatic cells showed that some of the localized noncoding and coding RNAs play a structural (translation independent) role in maintaining the integrity of microtubule and microfilament cytoskeleton and/or may function in protein folding or as a scaffold for the assembly of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…Thus, VegT structural RNA, which is also localized RNA, would have been a perfect player in the "bet-hedging" strategy of evolution (Dobrzynski et al 2011). On the basis of the many discoveries of new localized RNAs with potential roles in the organization of cellular architecture and function (Lecuyer et al 2007), we can speculate that, by being the progeny of the original RNA-based world, the phenotype of a cell or organism can be regarded as being binary (Kloc 2008(Kloc , 2009Kloc et al 2011), i.e., the same structural and regulatory functions are executed by evolutionary ancient RNA-based pathways and, in parallel, by evolutionary younger and more sophisticated but more sluggish, protein-based responses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, VegT structural RNA, which is also localized RNA, would have been a perfect player in the "bet-hedging" strategy of evolution (Dobrzynski et al 2011). On the basis of the many discoveries of new localized RNAs with potential roles in the organization of cellular architecture and function (Lecuyer et al 2007), we can speculate that, by being the progeny of the original RNA-based world, the phenotype of a cell or organism can be regarded as being binary (Kloc 2008(Kloc , 2009Kloc et al 2011), i.e., the same structural and regulatory functions are executed by evolutionary ancient RNA-based pathways and, in parallel, by evolutionary younger and more sophisticated but more sluggish, protein-based responses.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated a novel structural role of coding and noncoding localized RNAs in the organization and maintenance of the cytokeratin cytoskeleton in Xenopus oocytes (Kloc 2008(Kloc , 2009Kloc et al 2005Kloc et al , 2007. A structural role for various RNAs has also been found in dividing Xenopus and HeLa cells and in Drosophila embryos (Blower et al 2005(Blower et al , 2007Jenny et al 2006;Lecuyer et al 2007).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The role of Plin2 is unclear. The protein is associated with lipid droplets (Chan et al 2007), but a structural role for the plin2 RNA has also been suggested (Kloc 2009). A different set of localized mRNAs are involved in vegetal microtubule organization and transport in the zebrafish zygote (Nojima et al 2010; Ge et al 2014), although with slightly different functions (see Sect.…”
Section: Origins Of Axial Polarity In the Egg And Early Embryomentioning
confidence: 99%